1997
DOI: 10.1111/j.1469-7793.1997.243bo.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of chronic hypoxia on renal function in the rat

Abstract: Studies were performed on rats that had been made chronically hypoxic (CH rats) in a normoxic chamber at 12% O2 for 3–5 weeks. Under Saffan anaesthesia, respiratory and cardiovascular variables, renal haemodynamics and renal function were recorded while the rats spontaneously breathed 12% O2 followed by a switch to air breathing for 20 min. Plasma renin activity was assessed by radioimmunoassay of angiotensin I. Plasma atrial natiruetic peptide (ANP) was indirectly assessed by measurement of cyclic GMP in urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
(62 reference statements)
2
11
0
1
Order By: Relevance
“…Similarly, in rats, diuresis and natriuresis [36] or antidiuresis and antinatriuresis [37] have been described. However, more recent evidence suggests that acute hypoxia in rats causes antidiuresis and antinatriuresis [38,39] and that chronic hypoxia results in normal renal function [40]. Therefore, it is believed that a decrease in plasma volume is an unlikely contributor to the increased haematocrit in the present experiments.…”
Section: Discussionmentioning
confidence: 38%
“…Similarly, in rats, diuresis and natriuresis [36] or antidiuresis and antinatriuresis [37] have been described. However, more recent evidence suggests that acute hypoxia in rats causes antidiuresis and antinatriuresis [38,39] and that chronic hypoxia results in normal renal function [40]. Therefore, it is believed that a decrease in plasma volume is an unlikely contributor to the increased haematocrit in the present experiments.…”
Section: Discussionmentioning
confidence: 38%
“…2), indicating a stimulating effect of hypoxia on both AT 1 expression and receptor density in VSM cells. Chronic systemic hypoxia has been shown to activate RAS in a number of tissues, including the kidney, lung, heart, and pancreas (11,29,34). Leung et al (24) also recently reported an upregulation of AT 1 receptor expression and function in the carotid body by isobaric hypoxia.…”
Section: Discussionmentioning
confidence: 90%
“…In another investigation (18) concerning the effect of sympathectomy on long-term hypoxic rats, the authors gave insufficient information on their methods to allow us to comment on their findings of different sizes of blood vessels within the organ. We emphasise that the changes observed in the two compartments of the carotid body in our experiments occurred in the absence of an increase in venous pressure in vivo (19) and that during the perfusion-fixation procedure we used, retrograde filling and artificial distension of the organs venous microvasculature after death were prevented by raising the animals head just above the level of the thorax.…”
Section: Discussionmentioning
confidence: 99%